Aesthetic essays - Budd, Malcolm, 1941- (Oxford : Oxford University Press, 2008)
Malcolm Budd presents a selection of his work in aesthetics. Some essays deal with the abstract heart of aesthetics: issues such as the nature and scope of the aesthetic, the validity of aesthetic judgements, realism and anti-realism, pleasure and value, and the aim of art.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aesthetics